MIXED DIMENSIONAL PEROVSKITES HETEROSTRUCTURE FOR HIGHLYEFFICIENT AND STABLE PEROVSKITE SOLAR CELLS - Ge, Chuangye; Lu, Jian-Fang; Sing, Mriganka; Ng, Annie; Yu, Wei; Lin, Haoran; Satapath, Soumitra; Hu, Hanlin (Solar RRL, 2021)
Heterojunctions constructed upon multidimensional perovskites (1D/3D or 2D/3D) has emerged as an effective approach to improve the photovoltaic performance and stability of perovskite solar cells (PSCs). Herein, 1D trimethyl sulfonium lead triiodide (Me3SPbI3) 1D Me3SPbI3 nanoarrays are successfully synthesized via a two-step method in aqueous condition, which reflects excellent water resistivity and environmental stability. By incorporating this 1D Me3SPbI3 into lead halide 3D perovskites, heterostructural 1D/3D perovskite photoactive layer with improved morphology, crystallinity, enhanced photoluminescence lifetime, and reduced carrier recombination in comparison to its 3D counterpart is obtained. Moreover, an efficient and stable 1D/3D PSCs with power conversion efficiency (PCE) of 22.06% by using this 1D/3D perovskite are demonstrated. It noticeably maintained 97% of their initial efficiency after 1000 h storage under ambient condition (RH≈50%) without encapsulation. Our study opens up the design protocol for the development of next-generation highly efficient and stable perovskite solar cells.
Keywords: Type of access: Open Access; perovskite solar cells